Study of the Phenolic Composition of Shiraz Red Grape Cultivar (Vitis vinifera L.) Cultivated in North-eastern Thailand and its Antioxidant and Antimicrobial Activity - Butkhup, L.; Chowtivannakul, S.; Gaensakoo, R.; Prathepha, P.; Samappito, S. (South African Journal of Enology and Viticulture, 2016)
The seed, skin and whole grape extract of the red grape cultivar Shiraz, which is widely cultivated in Northeastern Thailand, were investigated. Total phenolic, total flavonoid and total monomeric anthocyanin content ranged from 48.04 to 116.73 g GAE/100g db (dry weight base), 74.82 to 258.69 mg CE/g db, and 5.06 to 55.45 mg/100g db, respectively. Dimeric procyanidin (119.56–484.08 mg/100g db), (+)-catechin (52.30–231.92 mg/100g db), (–)-epicatechin (27.92–174.10 mg/100g db), and gallic acid (4.42–27.80 mg/100g db) were found to be the main flavanols that were present in the seed. Rutin and trans-resveratrol were present in amounts of between 21.13 and 40.05 and 2.85 and 3.60 mg/100g db respectively. All extracts showed remarkable DPPH radical-scavenging activity (EC50), ranging from 0.47 to 2.10 μg/mL. Methanolic extract from the seed and skin were also active against all Gram-positive bacteria, but these exerted less of an inhibiting effect on the growth of the tested Gram-negative bacteria. The activity of the methanolic extract of the seed was effective against B. cereus ATCC 11778, B. subtilis ATCC 6633 and S. faecalis TISTR 459.